Ubiquitin family modifiers and the proteasome: Reviews and Protocols - Dohmen, R. Jürgen; Scheffner, Martin (Methods in molecular biology, 2012)
Three Decades of Studies to Understand the Functions of the Ubiquitin Family -- Structure and Evolution of Ubiquitin and Ubiquitin-Related Domains -- Deciphering Tissue-Specific Ubiquitylation by Mass Spectrometry -- Analysis of Cellular SUMO and SUMO-Ubiquitin Hybrid Conjugates -- Recombinant Reconstitution of Sumoylation Reactions In vitro -- Reconstitution of SUMO-Dependent Ubiquitylation In vitro -- Detection and Analysis of FAT10 Modification -- Isolation of NEDDylated Proteins in Human Cells -- The ISG15 Conjugation System -- Pupylation: Proteasomal Targeting by a Protein Modifier in Bacteria -- Role of UbF Family Modifiers and their Binding Proteins in Cell Signaling -- Isolation of Ubiquitylated Proteins using Tandem Ubiquitin-Binding Entities (TUBEs) -- Using Linkage-Specific Monoclonal Antibodies to Analyze Cellular Ubiquitination -- Measuring Rates of Ubiquitin Chain Formation as a Functional Readout of Ligase Activity -- Synthesis and Analysis of K11-Linked Ubiquitin Chains -- Synthesis and Analysis of Linear Ubiquitin Chains -- Detection and Quantitation of SUMO Chains by Mass Spectrometry -- Bioinformatical Detection of Recognition Factors for Ubiquitin and SUMO -- Surface Plasmon Resonance to Measure Interactions of UbFs with Their Binding Partners -- Identifying and Studying Ubiquitin Receptors by NMR -- Exploring the Role of p97 and its UBX-Domain Cofactors Through Identification of Their Interacting Proteins -- Assembly and Function of the Proteasome -- Using Native Gel Electrophoresis and Phosphofluoroimaging to Analyse GFP-tagged Proteasomes -- Disulfide Engineering to Map Subunit Interactions in the Proteasome and Other Macromolecular Complexes -- Using DNA Damage Sensitivity Phenotypes to Characterize Mutations Affecting Proteasome Function -- Analysing Properties of Proteasome Inhibitors using Kkinetic and X-Ray Crystallographic Studies -- Immunoproteasome-Specific Inhibitors and Their Application -- Binding of Ubiquitin Conjugates to Proteasomes as Visualized with Native Gels -- Affinity Purification of Mmammalian 26S Proteasomes Using an Ubiquitin-Like Domain -- Using siRNA Techniques to Dissect Proteasome Assembly Pathways in Mammalian Cells -- Reconstitution of PA700, the 19S Regulatory Particle, from Purified Precursor Complexes -- Cellular Responses to Misfolded Proteins and Protein Aggregates -- Live-Cell Imaging of Ubiquitin-Proteasome System Function -- Analysis of Chaperone-assisted Ubiquitylation -- Use of CPY* and its Derivatives to Study Protein Quality Control in Various Cell Compartments -- Assays to Measure ER-Associated Degradation in Yeast -- SDS-PAGE Techniques to Study Ubiquitin-Like Conjugation Systems in Yeast Autophagy -- Analysis of Ubiquitin-Dependent Proteolysis in C. elegans -- Structural Insights into Functional Modes of Proteins Involved in Ubiquitin Family Pathways -- Identification and Application of NEDD8 E1 Inhibitors -- Formation of Ubiquitin Dimers via Azide Alkyne Click Reaction -- Synthesis of Atypical Diubiquitin Chains -- TIPI - TEV Protease-Mediated Induction of Protein Instability -- PROTAC-Induced Proteolytic Targeting.
Keywords: Aufsatzsammlung; Proteasom; Ubiquitin